The Role of Ecological Innovations in the Modernization of the Economy of Uzbekistan (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the role and effectiveness of green innovations in the modernization of the economy. It also presents the current application of green innovations and the ongoing processes in Uzbekistan. In addition, the impact of environmental technologies on GDP is shown using statistical analysis. The article is written in an analytical approach based on scientific literature and international experience.
Keywords: Modernization; green innovations; green technologies; energy sources; increasing energy efficiency; environmental protection; solar panels, waste recycling